Opioid and benzodiazepine prescription among patients with cirrhosis compared to other forms of chronic disease - Monica A Konerman; Mary Rogers; Brooke Kenney; Amit G Singal; Elliot Tapper; Pratima Sharma; Sameer Saini; Brahmajee Nallamothu; Akbar Waljee (BMJ Open Gastroenterology, 2019)
ObjectiveData on patterns and correlates of opioid and benzodiazepines prescriptions among patients with chronic conditions are limited. Given a diminished capacity for hepatic clearance, patients with cirrhosis represent a high risk group for use. The aim of this study was to characterise the patterns and correlates of prescription opioid, benzodiazepine and dual drug prescriptions among individuals with common chronic diseases.DesignAnalysis of Truven Marketscan database to evaluate individuals with drug coverage with cirrhosis (n=169,181), chronic hepatitis C without cirrhosis (n=210 191), congestive heart failure (n=766 840) or chronic obstructive pulmonary disease (n=1 438 798). Pharmacy files were examined for outpatient prescriptions.ResultsPatients with cirrhosis had a significantly higher prevalence of opioid prescriptions (37.1 per 100 person-years vs 24.3–26.0, p≤0.001) and benzodiazepine prescriptions (21.3 per 100 person-years vs 12.1–12.9, p<0.001). High dose opioid prescription (>90 daily oral morphine equivalents) (29.1% vs 14.4%, p<0.001) and dual opioid and benzodiazepine prescription (17.5% vs 9.6%–10.5 %, p<0.001) were also significantly more prevalent in cirrhosis. High dose opioid prescription was greater in men, individuals ages 40–59, in the Western USA, and among those with a mental health or substance abuse condition. Dual opioid and benzodiazepine prescription were highest among those with alcoholic cirrhosis and middle aged-adults.ConclusionPersons with cirrhosis have significantly higher rates of prescription opioid and benzodiazepine prescription compared to others with chronic diseases despite their high risk for adverse drug reactions. Demographics and mental health or substance abuse history can help identify high risk groups to target interventions.